Responsibility for preventing and repairing damage to the environment - Jaworowicz-Rudolf, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The study introduces the rules of liability for failure to perform an obligation to prevent damage to the environment and an obligation to repair damage to the environment, which is subject to regulation by the Act of 2007 on the prevention of environmental damage and the repair of damage to the environment. It is primarily the responsibility of an administrative nature. The author emphasizes a narrow approach by the legislature to the concept of damage to the environment and the complexity of the issue of liability in case of breach of the environment or its element.